If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 3) + -2 = 16 Reorder the terms: 5(3 + x) + -2 = 16 (3 * 5 + x * 5) + -2 = 16 (15 + 5x) + -2 = 16 Reorder the terms: 15 + -2 + 5x = 16 Combine like terms: 15 + -2 = 13 13 + 5x = 16 Solving 13 + 5x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 5x = 16 + -13 Combine like terms: 13 + -13 = 0 0 + 5x = 16 + -13 5x = 16 + -13 Combine like terms: 16 + -13 = 3 5x = 3 Divide each side by '5'. x = 0.6 Simplifying x = 0.6
| 6n+4n=-7n | | 6n-(n+9)=3n+10+2n-19 | | 9(x-3)=8+2x | | 2x(4y+3x)= | | 5-8b=-10 | | 3/5x5 | | 8x+3=-5+6x+14 | | -1+4x=4x+7 | | n-(-11)=-6 | | -(4x-7y+2)= | | (7/x)=(1/0.5) | | 6y+1=7y+4 | | -x-4=-3x-16 | | -10n+3(8+n)=-6(n-4) | | 3^2/n | | 12t^2+6t-15=0 | | 2x+18=30+x | | a+2a+a+2a=180 | | 5x-8+4x+8=AC | | 3p+5=13 | | 6-3(x+5)=3(x-1) | | 3M-2=3M+1 | | 49x+89=9307 | | x-1.8=2.7 | | 3x+8=7x-20 | | V^2-4v-7=0 | | (3x-3)+(x-3)= | | x/5+7=17 | | 5x-2+2x+6x=67 | | 3x=18-(x-6)*2 | | 4t^9(t-t^2+8t^3)= | | -(x+3)=-6x-33 |